Spatial patterns and socio-environmental determinants of gonorrhea incidence in China - Hu, Ke; Yang, Xingjin; Cai, Yu; Li, Chaojie; Zhang, Xing; Xiao, Di; Yu, Mingyang (Frontiers in Public Health, 2025)
IntroductionGonorrhea is a major sexually transmitted infection in China, showing distinct regional clustering and spatial heterogeneity. Understanding its geographical distribution and influencing factors is crucial for targeted prevention.MethodsWe analyzed 2022 gonorrhea incidence across 31 Chinese provinces using both traditional and spatial statistical approaches, including descriptive statistics, spatial autocorrelation, multiple linear regression (MLR), and spatial error models (SEM). Factors from five categories—economic, demographic, environmental, educational, and healthcare-related—were examined. The Geodetector method was additionally used to assess factor contributions and interactions.ResultsThree key findings emerged: (1) Significant regional disparities in gonorrhea incidence were observed, with high-high clusters detected in southern provinces and low-low clusters in northern regions.; (2) SEM outperformed MLR, confirming stronger effects of illiteracy rate, bed utilization rate, sex ratio, and PM2.5 concentration while demonstrating better model fit (higher R2, log-likelihood; lower AIC); (3) Sex ratio was identified as a core determinant, with interaction effects (particularly bed utilization rate and sex ratio) amplifying individual impacts.ConclusionThese results support spatially tailored intervention strategies that integrate sociodemographic and environmental factors for effective gonorrhea prevention.